Estudio comparativo del acabado superficial obtenido en el proceso de coloreado por inmersión y coloreado electrolítico con corriente alterna de una aleación de aluminio aa6061 anodizado - Cabrera Escobedo, Carlos Alexander; Gutierrez Vargas, Jose Martin (2019)
The surface finish of two different processes of coloring, immersion coloring and electrolytic coloring with alternating current, of anodized AA 6061 aluminum specimens has been evaluated to determine the process that produces the best color quality of the anodic layer formed during anodization. Rectangular specimens 0.5 cm thick, 5 cm long and 2.5 cm wide were used, with a total exposed area of 0.325 dm2. For the anodization process, a solution of sulfuric acid with a concentration of 20% was used, at an amperage of 1.5 A / dm2 and a time of 30 minutes. For immersion coloring a solution of an organic dye, cochineal carmine at a concentration of 15 g / L, at a temperature of 90 to 95 ° C for a time of 10 minutes was used. For the electrolytic coloring a solution of Nickel Sulfate heptahydrate was used: 300 g / L, Nickel Chloride hexahydrate: 60 g / L and Boric Acid: 30 g / L; at an alternating current density of 1.1 A / dm2 for a time of 5 minutes. The specimens colored by the immersion process acquire a fuchsia color whose hue is variant and also their coloring is superficial because the dye is deposited on the surface of the pores of the anodic layer. The specimens colored by the electrolytic coloring process acquire a grayish beige color whose coloring of the anodic layer is more consistent, of greater hue and depth because the metallic particles of the dye are deposited at the base of the pores formed during the process of anodization Likewise, it is determined that the best surface finish is obtained with electrolytic coloring with alternating current due to its better uniformity and color consistency. Keywords: immersion coloring, electrolytic coloring, AA 6061 Aluminum Anodized